Bridging pedagogy and technology: a systematic review of immersive virtual reality's potential in climate change education - Tisoglu, Secil; Sonmez, Elif; Kaya, Kadir Yucel; Et, Suemeyra Zeynep (Routledge Journals, Taylor & Francis Ltd, 2025)
Climate change education (CCE) has a complex structure that includes certain pedagogical, methodological, and interdisciplinary elements, highlighting some challenges to scrutinize. To address these challenges, it is crucial to explore the potential of advanced technologies, such as immersive virtual reality (IVR), which can concretize, visualize, and make complex climate change phenomena more accessible. Despite its promise, IVR remains underexplored in CCE as a pedagogical method, with limited practical applications, pedagogical frameworks, or empirical outcomes. This systematic review across Web of Science, Scopus, ERIC, and Science Direct databases examines 19 studies that integrate IVR with climate change content, evaluating them from an educational standpoint across technological, pedagogical, and content components. Findings reveal that IVR can be a powerful tool for CCE when combined with constructivist approaches, such as inquiry-based learning, and when system features like interaction modalities are leveraged to enhance engagement and interaction. The review highlights IVR's potential to foster cognitive and affective outcomes as well as the gaps in the field, which overlook the behavioral outcomes and the extent of climate change issues concerning social, political, and cultural perspectives. We provide practical recommendations to explore how IVR could address climate change-related issues and improve pedagogical practices in CCE.
Keywords: Climate change; immersive virtual reality; pedagogy; climate change education; SDG 13: Climate action